Antiques Trade Gazette - Turnbull, Ivor (Londen : Metropolis Ltd., 1971)
Antiques Trade Gazette is a London-based weekly publication and website serving the art and antiques community. The print publication has around 16,000 subscribers (2015),[1] though its publisher also derives substantial revenues from online auction sites (Wikipedia)
Https://www.antiquestradegazette.com
Https://en.wikipedia.org/wiki/Antiques_Trade_Gazette
Engels
Tijdschriften
Keywords: veilingen; kunsthandel; antiquariaten; antiek